2015
DOI: 10.1111/dote.12341
|View full text |Cite
|
Sign up to set email alerts
|

Esophagus cancer and occupational exposure to asbestos: results from a meta-analysis of epidemiology studies

Abstract: The relationship between occupational asbestos exposure and esophagus cancer (EC) is not fully understood. We performed a meta-analysis to quantitatively assess the association. We systematically searched databases of PubMed, EMBASE, and Web of Science for studies with quantitative estimates of asbestos exposure and EC mortality. Pooled standardized mortality ratios (SMRs) and their corresponding 95% confidence intervals (CIs) were calculated. Twenty cohort studies on EC and asbestos exposure were included in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…The International Agency for Research on Cancer (IARC) Working Group concluded that asbestos causes mesothelioma and cancer of the lung and larynx 3. Positive associations have been observed between exposure to all forms of asbestos and cancer of the pharynx,30 31 hypopharynx,32 larynx,33 34 oesophagus35 36 and stomach 37 38. In this study, we observed that nephrite processing increases the mortality risk from cancer in the same sites.…”
Section: Discussionsupporting
confidence: 62%
“…The International Agency for Research on Cancer (IARC) Working Group concluded that asbestos causes mesothelioma and cancer of the lung and larynx 3. Positive associations have been observed between exposure to all forms of asbestos and cancer of the pharynx,30 31 hypopharynx,32 larynx,33 34 oesophagus35 36 and stomach 37 38. In this study, we observed that nephrite processing increases the mortality risk from cancer in the same sites.…”
Section: Discussionsupporting
confidence: 62%
“…Based on description from Institute of Medicine (US) Committee on Asbestos in 2006, the evidence related to association between asbestos and esophageal cancer was insufficient [ 54 ]. In contrast, Li et al had conducted a meta-analysis through 20 cohort studies and they found positive association between esophageal cancer and asbestos exposure [ 55 ]. However, we made a more comprehensive search from 1963 to 2017, and finally included 34 studies which generated 36 SMR for meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…A meta‐analysis conducted in 2006 and based on 25 cohort studies and three case‐control studies, showed neither a link nor a dose‐effect relationship between asbestos exposure and esophageal cancer . Nevertheless, a recent meta‐analysis by Li et al based on 20 studies of esophageal cancer mortality among workers exposed to asbestos, published between 1988 and 2014, concluded that high levels of asbestos exposure could contribute to significantly elevated risks of mortality from esophageal cancer. The authors demonstrated an elevated risk in the pooled estimate for esophageal cancer mortality in relation to asbestos exposure (SMR = 1.24 [1.12‐1.37]).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, according to the IARC (International Agency for Research on Cancer), this association is uncertain. Nevertheless, a meta‐analysis, conducted in 2016 concluded that high levels of exposure to asbestos may contribute toward a significantly higher risk of mortality from esophageal cancer.…”
Section: Introductionmentioning
confidence: 99%